Implementasi Perlindungan Hak Asasi Manusia Terhadap Pemeriksaan Dalam Proses Penyidikan - Komang Dara Trimarlina; I Nyoman Sujana; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2019)
Protection and respect for human rights is a main pillar in any State of law, to provide legal protection against a suspect, then the law number 8 of year 1981 on the law of criminal procedure should be realized, in particular, in the investigation of criminal cases, special interrogation frequently occurs in the arbitrary actions of the investigator against the suspects, who allegedly committing a criminal offence. Violence, intimidation and other forms of coercion against suspects in the process of investigation proved very difficult, legal protection for suspects in the process of investigation, the right to give information freely without pressure from any party the right to obtain legal assistance at every level 1 inspection.) How is the implementation of rights protection-human rights (human rights) in the process of examination of the suspect at the level of investigation? And 2) Rights-rights of anything owned by a suspect in the Investigation Process. This study uses empirical research methods. The position of the suspect and the accused in the CRIMINAL PROCEDURE CODE is as a subject, which in any examination must be treated in a position of human being has the dignity, dignity and self-suspect it doesn't look as rights object and dignity human dignity with arbitrary. Laws and regulations in Indonesia have set the existence of some of the rights of a person who is declared as suspects that must be respected and in respect by every law enforcement in Indonesia's judicial process.